The Impact of Physical Activities on Cognitive Performance among Healthy Older Individuals - Klimova, Blanka; Dostalova, Radka (Brain sciences, 2020)
The population is aging in developed countries. This aging process results in many changes, both physical and mental. Over the years, there has been a gradual decline in the level of cognitive functions closely related to the ageing process, which is most often connected with ageing diseases such as dementia. So far, pharmacological treatment has not yet been able to cure this neurological disorder. Health policies around the world seek to find alternative programs and strategies to help a healthy population prevent cognitive decline and prolong active life. One such strategy appears to be physical activity. The aim of this review is to discuss the impact of physical activity on cognitive performance among healthy older individuals. The methodology of this study is based on a systematic electronic literature search of available studies found in three databases: PubMed, Web of Science and Scopus. The findings suggest that any physical activity in older age seems to have a positive impact on the improvement of cognitive function. Furthermore, it appears that dancing, due to its multiple mechanisms, might have the biggest effect on the enhancement of cognitive performance in healthy older individuals. However, controlled clinical trials of physical activity intervention in older adults are rare. Therefore, further research in this area (particularly on the amount of physical activity, its intensity and type) is needed.
Keywords: healthy older people; effect; aerobic exercises; physical activities; dance; cognitive functions